Media Interaktif sebagai Inovasi Pembelajaran IPA bagi Peserta Didik Kelas IV SD pada Materi Wujud Zat dan Perubahannya - Eka Maulidia; Muhammad Suwignyo Prayogo; Tsania Nailal Ilfa; Adellia Saputri (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Science learning in elementary schools plays a vital role in fostering scientific thinking, curiosity, and critical thinking skills from an early age. However, classroom practices are still dominated by conventional methods that make students passive and less motivated, which affects their understanding of abstract concepts such as the states of matter and their changes. This study aims to describe the effectiveness of using Canva as an interactive learning medium to enhance the motivation and learning outcomes of fourth-grade elementary school students on the topic of states of matter and their changes. The research employs a qualitative descriptive method through literature review and theoretical experimentation. The study involved reviewing various scientific sources and conducting a simulated Canva-based learning activity that visualized changes in the states of matter through images, animations, and simple classroom experiments. The findings reveal that using Canva encourages active student participation, clarifies abstract science concepts, and creates an engaging learning experience. Canva has proven to be an effective and innovative medium that supports the principles of the Merdeka Curriculum, emphasizing creativity, collaboration, and independent learning.